DEVELOPMENT OF CONTEXTUAL TEACHING AND LEARNING (CTL) BASED LEARNING MATERIALS TO FACILITATE STUDENTS IN IMPROVING CRITICAL THINKING ABILITY IN REDOX AND ELECTRO CHEMICAL TOPICS - Novia Prihastyanti; Deni Ainur Rokhim; Subandi Subandi; Darsono Sigit (Jurnal Pembelajaran Sains, 2020)
Some high school students still experience difficulties in studying chemistry, one of which is redox and electrochemistrytopics, which is very closely related to daily life. Besides that students 'understanding of the application of the material in daily life and students' critical thinking skills are low. This happens because students learn by rote caused by learning material that is contextual. Therefore it is necessary to develop learning materials based on Contextual Teaching and Learning to facilitate students in improving students' critical thinking skills on redox and electrochemistry topics. The development method used is basically the development model of the Four-D Model (4D Model by Thiagarajan) which consists of 4 stages, namely Define, Design, Develop, and Disseminate. Teaching material that has been developed in the form of teaching material products based on Contextual Teaching and Learning on redox and electrochemical materials to facilitate critical thinking skills of high school students. This teaching material consists of student books, teacher books, and learning videos. Based on the validation test and readability test on student books, teacher books, and learning video the results of the obtained scores were 86%, 89%, 82%, and 83%, respectively. This shows that the learning material resulting from the development is very suitable to be used in learning on the material at the high school level.